Las Técnicas Audiovisuales Y Su Influencia En Los Procesos Educacionales Entre Docentes Y Estudiantes De La Escuela General Básica Gastón Campuzano Guerrero De La Parroquia San Camilo Del Cantón Quevedo Provincia De Los Ríos. - Carriel Tejena, Jimmy E. (2015)
The development of education through experienced several changes since its structure to its application; the influence of internal and external factors has resulted in the teaching-learning process suffers radical changes, the use of audiovisual techniques and link the student with the acquisition of their own knowledge. As the problem is formulated in the thesis research, teaching resources in the teaching-learning process are not being properly used to properly relate the themes of class teacher to students, considered the most important elements in the process - learning, allowing students to approach the reality of what teaching is offering a more accurate idea of the facts or phenomena studied. When exposed in this work, the emerging need application of audiovisual techniques such as educational learning processes related to theories exposed remains because evidence that teaching with audiovisual means students can better grasp the idea, understand the issue and be related. The education received by people in the growth and development of its existence is uneven, the application of innovative techniques by the teacher where all are integrated and interact is the key to educational processes framed in good living and integration group.